2003
DOI: 10.1146/annurev.ento.48.091801.112756
|View full text |Cite
|
Sign up to set email alerts
|

The Genome Sequence and Evolution of Baculoviruses

Abstract: Comparative analysis of the complete genome sequences of 13 baculoviruses revealed a core set of 30 genes, 20 of which have known functions. Phylogenetic analyses of these 30 genes yielded a tree with 4 major groups: the genus Granulovirus (GVs), the group I and II lepidopteran nucleopolyhedroviruses (NPVs), and the dipteran NPV, CuniNPV. These major divisions within the family Baculoviridae were also supported by phylogenies based on gene content and gene order. Gene content mapping has revealed the patterns … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
380
0
23

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 426 publications
(413 citation statements)
references
References 118 publications
10
380
0
23
Order By: Relevance
“…Two transcriptionspecific genes lef-10 and lef-12, previously identified in AcMNPV and BmNPV, were also present in MaviNPV as ORFs 39 and 30, respectively. In addition, MaviNPV encodes homologues of 39K (ORF25), lef-6 (ORF19) and lef-11 (ORF26), which are present in all sequenced lepidopteran baculoviruses (Herniou et al, 2003). Although AcMNPV, BmNPV and MaviNPV are all closely related, we note that while the amino acid identity of AcMNPV lef-6 and BmNPV lef-6 aa is 93 %, the identity between MaviNPV lef-6 aa and AcMNPV or BmNPV is only 34-35 %.…”
Section: Resultsmentioning
confidence: 87%
See 4 more Smart Citations
“…Two transcriptionspecific genes lef-10 and lef-12, previously identified in AcMNPV and BmNPV, were also present in MaviNPV as ORFs 39 and 30, respectively. In addition, MaviNPV encodes homologues of 39K (ORF25), lef-6 (ORF19) and lef-11 (ORF26), which are present in all sequenced lepidopteran baculoviruses (Herniou et al, 2003). Although AcMNPV, BmNPV and MaviNPV are all closely related, we note that while the amino acid identity of AcMNPV lef-6 and BmNPV lef-6 aa is 93 %, the identity between MaviNPV lef-6 aa and AcMNPV or BmNPV is only 34-35 %.…”
Section: Resultsmentioning
confidence: 87%
“…All 126 MaviNPV ORFs have an assigned function or homologues in other baculoviruses. The 29 genes shared by all baculovirus genomes, including the dipteran and hymenopteran baculoviruses (Herniou et al, 2003;Garcia-Maruniak et al, 2004), were also found in the MaviNPV genome. The 126 predicted ORFs are encoded by 92 % of the MaviNPV genome; the rest is made up of intergenic spaces and hrs.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations